PROPAGATION OF RAYLEIGH WAVE IN SOLIDS WITH FILLET TRANSITIONS - A. R. Baev; M. V. Asadchaya; O. S. Sergeeva; G. E. Konovalov (Приборы и методы измерений, 2015)
New distinctive features of the elastic wave excitation and propagation when the Rayleigh wave probes used have been discussed. It was principally shown that such probes can be used not only to find surface defects but to find vertically oriented defects of the low reflection ability. Experimental dependences of the coefficient transformation of Rayleigh wave into edge waves vs. radius of the fillet transition have been got. Influence of the «accompanying» transverse mode excited simultaneously with Rayleigh wave on the resulting acoustic field formation in the projection volume have been investigated.